Knowledge of COVID-19 and online purchase intention: the role of health protocol and fulfilment - Sukardi, Sukardi; Ismanto, Deny (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2022)
Purpose – This study analyses the relationship between knowledge of COVID-19 and the application of health protocols, fulfilment in the pandemic era and online purchase intention. This study also analyses the effect of health protocol and fulfilment on online purchase intention. Design/methodology/approach – This study is a quantitative study with a student population in Yogyakarta. From the total population, 170 respondents were taken by random sampling method. The data in this study are primary data obtained through the distribution of questionnaires. From the data obtained, analysis was carried out using the Structural Equation Model method using Partial Least Square with Smart-PLS software. Findings – The results of the analysis in this study indicate that knowledge of COVID-19 is able to have a significant influence on the implementation of health protocols and fulfilment, but knowledge of COVID-19 is not able to significantly influence online purchase intention. The results of the analysis also state that the health protocol is not able to have a significant effect on online purchase intention in students, while fulfilment is able to provide a significant influence on online purchase intention. Research limitations/implications – For further research, it is expected to be able to examine more deeply online purchase intentions across generations and compare them. Further research is also expected to include several other variables that have a role in online shopping behaviour. Practical implications – The results of the analysis in this study also provide recommendations for business people in this pandemic era to emphasize online buying and selling services. Online marketing is also more recommended because the more people understand about COVID-19, the less they do activities outside the home, so the most effective marketing is through social media which is accessed by the public every day. Originality/Value – In contrast to previous studies, this study proposes a model of people's behaviour in shopping online. The analysis in this study formulates the relationship between knowledge of COVID-19, health protocol, fulfilment and online purchase intention.